A matter of consistency: Dignity and personhood in human rights biolaw. (March 2014) - Finegan, Thomas
Between 1997 and 2005, four formal international law documents were promulgated involving the intersection of human rights law with bioethics. Underpinning and animating each of these legal texts is an implicit philosophy of human dignity and personhood. This article makes explicit the operative philosophy in each of the documents and questions whether the four texts in question evince an overarching, consistent approach to dignity and personhood. The article proceeds by distinguishing between the two broad and incompatible ways of understanding both of the core categories at issue: intrinsic and extrinsic dignity, and Boethian and Lockean personhood. An exegesis of the legal texts reveals the mutually supportive role intrinsic dignity and Boethian personhood play throughout the four documents. The exegesis highlights the implications this philosophy has for issues involving nascent human life, implications not always overtly stated in the legal texts themselves, though invariably—at a minimum—hinted at by these texts.